2013
DOI: 10.1044/1058-0360(2012/11-0052)
|View full text |Cite
|
Sign up to set email alerts
|

Specific Language Impairment and Executive Functioning: Parent and Teacher Ratings of Behavior

Abstract: Parent and teacher perceptions of executive functioning in children with SLI align with prior findings of executive deficits that have been documented on neuropsychological assessments and experimental tasks. Furthermore, the results provide additional supporting evidence of the relationship between language abilities and executive functioning in early child development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…Mirman & Britt [22] note that post-stroke performance on certain EF tests correlates with impairments on lexical-semantic tasks such as picture naming, word-to-picture matching and picture-picture matching (see also [59]). In a similar vein, EF deficits have been reported in children with specific language impairment [60,61].…”
Section: (E) Executive Functions: Attention and Inhibitionmentioning
confidence: 73%
“…Mirman & Britt [22] note that post-stroke performance on certain EF tests correlates with impairments on lexical-semantic tasks such as picture naming, word-to-picture matching and picture-picture matching (see also [59]). In a similar vein, EF deficits have been reported in children with specific language impairment [60,61].…”
Section: (E) Executive Functions: Attention and Inhibitionmentioning
confidence: 73%
“…Results of the only experimental study we know of showed that preschoolers with PLI have difficulty inhibiting prepotent responses and irrelevant distractions (Spaulding, 2010). A questionnaire study that used the Behavior Rating Inventory of Executive function-Preschool Version showed that children with PLI were rated as exhibiting significantly poorer executive functions relative to their peers with TD (Wittke et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Carlson, Mandell, and Williams (2004) found a significant correlation between performance on behavioral batteries of executive function and parent reports of language skills in 2-and 3-year-olds. Moreover, Wittke et al (2013) also identified a significant correlation between scores on the (Gioia, Espy, & Isquith, 2003), parent and teacher ratings, and language abilities as assessed by the Clinical Evaluation of Language Fundamentals Preschool-Second Edition (CELF P-2; Wiig, Secord, & Semel, 2004) in preschoolers with TD and with PLI.…”
Section: The Impact Of Language On Executive Function In Preschoolmentioning
confidence: 99%
See 1 more Smart Citation
“…And, this estimate correlates with the level of speech abilities of the child (Wittke et al, 2013). Yang and Gray find that 4-5-year-old children with primary speech impairment show deficits in EF (working memory and cognitive flexibility) compared with their peers with typical development, but they have no impulsivity control impairment (Yang & Gray, 2017).…”
Section: Problem Statementmentioning
confidence: 99%